SAT0222 B Cell Depletion Therapy in Systemic Sclerosis Associated Interstitial Lung Disease. A Multicenter, Open Label, Comparative Study with A Follow up of 94 Patient-Years. (15th July 2016) - Melissaropoulos, K.; Daoussis, D.; Sakellaropoulos, G.; Antonopoulos, I.; Markatseli, T.E.; Simopoulou, T.; Georgiou, P.; Andonopoulos, A.P.; Drosos, A.A.; Sakkas, L.; Liossis, S.-N.
Abstract : Background: We have previously shown that rituximab (RTX) may favorably affect lung function and skin fibrosis in patients with systemic sclerosis (SSc). Objectives: To assess long term efficacy and safety of RTX in SSc compared to standard treatment. Methods: Fifty one patients with SSc associated interstitial lung disease were recruited and treated with RTX (n=33) or standard treatment (n=18). RTX cycles were repeated every 6 months throughout follow up apart from 6 patients where RTX was discontinued following 2 years of continuous treatment. Mean follow up was 2.9 years (range 1–7). Standard treatment consisted of azathioprine (n=2), methotrexate (n=6) and mycophenolate (n=10). Results: Patients in the RTX group showed an increase in FVC during the first year of treatment (mean ± SEM of FVC: 80.60 ± 3.69 vs 83.02 ± 3.37 at baseline vs 1-year, respectively, p=0.13); this beneficial effect was further augmented at 2 years (86.90 ± 4.72, p=0.04 compared to baseline). In sharp contrast, patients in the control group had no change in FVC during the first 2 years of follow up. At 2 years, the RTX group was numerically better than the control group; however, differences tended but did not reach statistical significance (p=0.063). At the 7 year time point patients in the RTX group had higher FVC compared to baseline (mean ± SEM of FVC: 91.60 ± 6.62, p=0.15 compared to baseline) in contrast to patients in the control group where FVC deteriorated (p<0.01, compared to baseline). Direct comparison between the 2 groups showed a significant benefit for the RTX group (p=0.013). DLCO also improved following 2 years of RTX treatment (mean ± SEM of DLCO: 59.22 ± 3.16 vs 61.51 ± 4.02 at baseline vs 2-years, respectively, p=0.05). In the standard treatment group DLCO constantly deteriorated throughout follow up. In 6 patients where RTX was stopped following 2 years of continuous treatment a decline in PFTs was evident. Improvement of skin thickening was found in both the RTX and the standard treatment group, however, direct comparison between groups strongly favored RTX at all time points (p=0.002, 0.015, 0.002, 0.053 0.029 for the 1, 2, 3, 4 and 5-year time point, respectively). In the RTX group, six cases of respiratory infection requiring hospitalization, one case of hepatitis B reactivation and one case of herpes zoster were recorded. Two patients were diagnosed with cancer (lung and prostate). Five deaths were recorded: end stage respiratory failure (n=2), lung cancer (n=1), sudden death (n=1), unknown (n=1). In the control group, five patients with respiratory and four patients with urinary infection were hospitalized. In four cases, infections were recurrent. Two deaths were reported due to respiratory infection. Conclusions: Our data indicate that continuous treatment with RTX has a beneficial effect on lung function and skin fibrosis in patients with SSc. Treatment was well-tolerated. Randomized controlled studies are highly needed. Disclosure of Interest: None declared